Progress on the formation dynamics of the layered circulation in the South China Sea. (February 2020) - Cai, Zhongya; Gan, Jianping; Liu, Zhiqiang; Hui, Chiwing Rex; Li, Junlu
Highlights: South China Sea has a three layer cyclonic-anticyclonic-cyclonic (CAC) circulation. The CAC circulation is constrained by the principle of Stokes theorem. The layered planetary vorticity flux through Luzon Strait drives the CAC circulation. Internal flow-topography interaction and vertical motion sustain the CAC circulation. Abstract: In the South China Sea (SCS), an alternating cyclonic-anticyclonic-cyclonic (CAC) circulation is recognized in the upper-middle-deep layers based on the principle of Stokes theorem. The CAC circulation is driven extrinsically by the East Asia monsoonal winds, a vertical sandwich-like inflow-outflow-inflow through Luzon Strait (LS) and intrinsically by the slope current-topography interaction. The understandings on the formation mechanisms of CAC circulation have been achieved based on different principles, and the physically solid interpretation on the CAC circulation need to be further clarified. In this paper, we review different dynamic perspectives from recent researches that describe the combined effects of surface wind forcing, lateral external forcing, and the intrinsic coupling among different layers. Our aim is to obtain a consistent understanding of the dynamics of the circulation in the SCS. The CAC circulation forms largely from the planetary vorticity flux that is extrinsically induced by the inflow-outflow-inflow through LS, which is predominantly balanced by the interaction between the CAC flow and bottom topography. Inside basin, the vertical motion dynamically links the circulation in three layers, and its spatial pattern has a strong impact on the basin circulation, particularly in the middle and deep layers. Vertical coupling of the layers occurs mainly over the slope because of the cross-slope motion due to interaction between strong slope current and topography. The internal layered circulation and intensified mixing, in turn, affect and maintain the layered current structure in LS. Based on the review of the forcing mechanisms, we offer perspectives for further investigations.